The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1080/1743873x.2016.1242590
|View full text |Cite
|
Sign up to set email alerts
|

The role of trails in the creation of tourist space

Abstract: Trails and routes are increasingly ubiquitous features within the tourism landscape and although their role and usefulness as applied tourism products has been analysed, they remain undertheorized within the academic literature. This article addresses this gap by exploring the role of trails within the socio-cultural construction of space. In particular, the potential function of trails in creating themed, static spaces is analysed and the concept of museumisation is employed to further illustrate the capacity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 47 publications
1
37
0
3
Order By: Relevance
“…As land-use is becoming increasingly diverse and where commercial and recreational interests compete for the same space [19,28], future research should continue to examine what role existing resources in multifunctional landscape can play in balancing such interests. As MacLeod [97] argued, the trail is under-theorised within scientific research and there are reasons to believe that the trail will become an increasingly important feature in the planning and management of natural areas through channeling and interpretation. Although the results from this specific study area are not generalizable, they are likely applicable to other landscapes, thereby possibly providing an introduction to further investigations of trails (or other resources) in the context of land-use conflict management.…”
Section: Discussionmentioning
confidence: 99%
“…As land-use is becoming increasingly diverse and where commercial and recreational interests compete for the same space [19,28], future research should continue to examine what role existing resources in multifunctional landscape can play in balancing such interests. As MacLeod [97] argued, the trail is under-theorised within scientific research and there are reasons to believe that the trail will become an increasingly important feature in the planning and management of natural areas through channeling and interpretation. Although the results from this specific study area are not generalizable, they are likely applicable to other landscapes, thereby possibly providing an introduction to further investigations of trails (or other resources) in the context of land-use conflict management.…”
Section: Discussionmentioning
confidence: 99%
“…Hiking tourism promotes a slow consumption of territory (an active form of slow tourism) through adapted routes, which are equipped in their immediate vicinity with heritage resources and specialized tourist services and facilities. However as various authors point out, the brief history of this form of tourism has shown that it is not enough to develop hiking holiday ideas based solely on the provision of high-quality facilities and services or involving the creation of routes through attractive, picturesque landscapes [23,24], it is also necessary to concentrate on the design and creation of memorable experiences within a dynamic setting [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Today trails and routes are increasingly commonplace tourism products that have remained under-theorised within the academic literature. MacLeod [2] suggested that trails possess characteristics that may lead to the further theming and museumisation of tourist spaces, creating static places of consumption aimed outwardly at the visitor economy. However, through the use of recent examples to illustrate the performance turn in tourism studies, MacLeod [2] proposes that trails can be utilised to increase visitors' and local communities' appreciation and active engagement with places.…”
Section: Introductionmentioning
confidence: 99%
“…MacLeod [2] suggested that trails possess characteristics that may lead to the further theming and museumisation of tourist spaces, creating static places of consumption aimed outwardly at the visitor economy. However, through the use of recent examples to illustrate the performance turn in tourism studies, MacLeod [2] proposes that trails can be utilised to increase visitors' and local communities' appreciation and active engagement with places. In particular, the flexibility of trails to incorporate both tangible and more experiential place-based features in their storytelling is highlighted, suggesting that these popular attractions can contribute to a much more nuanced and rewarding experience of the place.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation